Local regulations for the use of artificial intelligence in the management of public records : a literature review - Svärd, Proscovia; Guerrero, Esteban; Balogun, Tolulope; Saurombe, Nampombe; Jacobs, Lorette; Henttonen, Pekka (Emerald, 2024)
Purpose This study investigated the regulatory landscape surrounding artificial intelligence (AI) in the context of e-government development. The purpose of this article is to identify record-keeping challenges, opportunities and weaknesses that emerge from AI loose regulation. The research focuses on Sweden, Finland and South Africa, examining the interplay between existing guidelines, recommendations and legal structures at various levels. Design/methodology/approach The research adopted comprehensive systematic and scoping literature reviews, encompassing academic papers, reports and legal documents, along with an analysis of non-academic sources relevant to the study. This methodological approach helped to obtain a deep understanding of the evolving AI regulatory frameworks. Findings There is currently limited research that focuses on the impact AI deployment has on the management of critical records in government administrations. Also, the findings reveal that AI regulatory environment varies from country to country. The European Union stands as a noteworthy example of a comprehensive framework for AI governance. In contrast, South Africa, while at its infancy stage, demonstrates potential initiatives and policies at different levels. There is emphasis on the need to focus on co-operation, skills development and uniform regulatory frameworks. Practical implications This research holds significant practical implications for policymakers, government bodies and stakeholders involved in AI governance. It emphasizes how crucial it is to incorporate AI alongside a solid records management system. The study advocates for strategic investments in education and skills development to enable individuals to navigate the complexities of AI governance. Originality/value This research adds to the existing body of knowledge by providing an examination of AI legislation in e-government in the context of public records management. The analysis helps to review literature and other research materials across different geographical areas. The study explores the distinctive strategies used by Sweden, Finland and South Africa. The recommendations offer policymakers and stakeholders suggestions on how to foster effective AI governance and innovation in the public sector but at the same time manage public records effectively.
Keywords: Public records; E-government development; artificial intelligence; legislation; electronic government; fi=Tietojärjestelmätiede|en=Information Systems|